Diet dichotomy between two migrant seabirds breeding near a high Arctic polynya. Issue 3 (22nd March 2017) - Pratte, Isabeau; Boadway, Kelly A.; Davis, Shanti E.; Maftei, Mark; Mallory, Mark L.
Abstract : High Arctic polynyas are predictable areas of open water, which offer long-distance migrant seabirds a reliable source of food during a period when they have to replenish and accumulate energy for reproduction. Investigating the interaction between species nesting sympatrically in the vicinity of polynyas should provide insights into the role that such oceanographic features play for pre-breeding seabirds. We used stable isotopes (δ 13 C and δ 15 N) to compare the diet of two ground-nesting seabirds, Sabine's gull ( Xema sabini ) and Arctic tern ( Sterna paradisaea ), nesting on an island adjacent to a recurring polynya in the Canadian high Arctic in 2008 and 2009. We show that, unlike Arctic terns, the diet of Sabine's gulls appears to include a non-negligible amount of terrestrially derived prey during early incubation, and that overall both species segregate their dietary niche during pre-laying and early incubation.